Contrasting Responses to Nutrient Enrichment of Prokaryotic Communities Collected from Deep Sea Sites in the Southern Ocean - Gerard T. A. Fleming; John W. Patching; David A. Pearce; David M. McCarthy (Biology, 2013)
Deep water samples (ca. 4,200 m) were taken from two hydrologically-similar sites around the Crozet islands with highly contrasting surface water productivities. Site M5 was characteristic of high productivity waters (high chlorophyll) whilst site M6 was subject to a low productivity regime (low chlorophyll) in the overlying waters. Samples were incubated for three weeks at 4 °C at in-situ and surface pressures, with and without added nutrients. Prokaryotic abundance increased by at least two-fold for all nutrient-supplemented incubations of water from M5 with little difference in abundance between incubations carried out at atmospheric and in-situ pressures. Abundance only increased for incubations of M6 waters (1.6-fold) when they were carried out at in-situ pressures and with added nutrients. Changes in community structure as a result of incubation and enrichment (as measured by DGGE banding profiles and phylogenetic analysis) showed that diversity increased for incubations of M5 waters but decreased for those with M6 waters. Moritella spp. came to dominate incubations carried out under in-situ pressure whilst the Archaeal community was dominated by Crenarchaea in all incubations. Comparisons between atmospheric and in situ pressure incubations demonstrated that community composition was significantly altered and community structure changes in unsuspplemented incubations at in situ pressure was indicative of the loss of functional taxa as a result of depressurisation during sampling. The use of enrichment incubations under in-situ conditions has contributed to understanding the different roles played by microorganisms in deep sea ecosystems in regions of low and high productivity.